2021
DOI: 10.3390/ma14195785
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Property of ZrO2-Added NiCrAlY Prepared by Ultrasonic-Assisted Direct Laser Deposition

Abstract: For improving the wear properties of NiCrAlY, the 10 wt %, 20 wt % and 30 wt % ZrO2-added NiCrAlY samples were prepared by ultrasonic-assisted direct laser deposition, respectively. The results showed that the ultrasonic-assisted direct laser deposition can realize the ZrO2-added NiCrAlY preparation. Furthermore, due to the cavitation effect and agitation of the ultrasound in the molten pool, ultrasonic-assisted could make the upper surface of the samples smoother and flatter, and it also improved the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Their yield ratios were 0.72 and 0.61, respectively. Theoretically, an increase in the yield ratio is reflected as a decrease in the deformation strengthening capability, and a corresponding decrease in the strain hardening index results in an increased risk of brittle failure [ 25 ]. According to their tensile curves, the elastic deformation stages of the two samples were highly consistent (stress–strain curves were linear, and the slopes were identical); however, the sample with 0.5 wt.% Y 2 O 3 exhibited a slightly higher tensile slope and better plasticity at the beginning of the plastic deformation stage.…”
Section: Resultsmentioning
confidence: 99%
“…Their yield ratios were 0.72 and 0.61, respectively. Theoretically, an increase in the yield ratio is reflected as a decrease in the deformation strengthening capability, and a corresponding decrease in the strain hardening index results in an increased risk of brittle failure [ 25 ]. According to their tensile curves, the elastic deformation stages of the two samples were highly consistent (stress–strain curves were linear, and the slopes were identical); however, the sample with 0.5 wt.% Y 2 O 3 exhibited a slightly higher tensile slope and better plasticity at the beginning of the plastic deformation stage.…”
Section: Resultsmentioning
confidence: 99%
“…A successful approach to overcome this problem is utilizing laser deposition technology along with ultrasonic vibration. Yi et al [96] used a direct laser deposition technique under ultrasonic vibration for the preparation of ZrO 2reinforced NiCrAlY coatings. Prior to employing the ultrasound-assisted technique, the obtained specimens exhibited undesirable macroscopic morphology with numerous oxide scales at the surface, which were spalled during the cooling period.…”
Section: Laser-cladded Coatingsmentioning
confidence: 99%
“…In 2020, Xie Tianhai et al did an experimental study on the removal of thermal barrier coatings via a plasma spraying method with abrasive water jets. The results showed that the erosion hole diameter and hole depth increased with the increase in abrasive concentration, jet pressure, punching time, and target distance, and the coating removal rate increased with the increase in abrasive hardness and particle size [23].…”
Section: Introductionmentioning
confidence: 98%